ANTI-BACTERIAL POTENTIAL OF SILK RECOVERED FROM ERIOVIXIA EXCELSA ( S IMON, 1889) S PIDER - H. M. Tahir; A. Sattar; S. Qamar; M. K. Mukhtar; I. Liaqat; M. A. Ali; A. Zaheer; N. Arshad; R. Yaqoob; S. Naseem (Journal of Animal and Plant Sciences, 2019)
Present study was designed with an aim to evaluate anti-bacterial potential of an orb-web spider Eriovixia excelsa. Live spiders were collected from the field and reared in the laboratory for harvesting silk. Disc diffusion methods was used to evaluate antibacterial potential of silk. Silk of E. excelsa showed negligible antibacterial activity against Pasteurella sp. and Staphylococcus sp. at all tested concentrations (i.e., 100%, 75%, 50% & 25%). However, spider silk inhibited the growth of Streptococcus sp.and Acinetobactor sp. Inhibitory potential of silk was increased with the increase in silk concentration. ANOVA followed by Tukey’s test revealed significant difference among treatments. It is concluded that silk of E. excelsa could be used to prepare antibiotics against Pasteurella sp. and Staphylococcus sp.
Keywords: Spider; Silk; Antibacterial potential; Disc diffusion; Eriovixia excelsa